Hotel and hospitality English : communicate confidently with guests - Seymour, Mike, ....- (London : Collins, 2011)
24 compact units cover a wide range of practical scenarios, such as meeting and greeting guests, taking orders at breakfast and at the bar, handling guest complaints and dealing with guest requests. 4-page unit includes an easy-to-follow photo story that deals with the topic of the unit and introduces key functional language. The pocket-sized course book also contains vocabulary lists for quick reference, practical examples of typical emails, an answer key and a pronunciation guide to further aid the self-study learner. The audio CD provides valuable listening practice to accompany each unit.
Keywords: Engels -- Toerisme; English language -- Conversation and phrase books (for restaurant and hotel personnel).; English language -- Textbooks for foreign speakers